2015
DOI: 10.1111/bjd.13646
|View full text |Cite
|
Sign up to set email alerts
|

Lifestyle and youthful looks

Abstract: Although associative in nature, these results support the notion that lifestyle factors can have long-term beneficial effects on youthful looks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 45 publications
(74 reference statements)
1
17
0
Order By: Relevance
“…The mean estimate of the age for each participant was used as the participant’s perceived age. The method used for generating perceived age has been tested in terms of its reliability and validity previous to this study (Gunn et al, 2015; Gunn et al, 2008; Gunn et al, 2009). In this study, the perceived age rating had a Cronbach’s alpha of α = .97, representing excellent interrater reliability.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The mean estimate of the age for each participant was used as the participant’s perceived age. The method used for generating perceived age has been tested in terms of its reliability and validity previous to this study (Gunn et al, 2015; Gunn et al, 2008; Gunn et al, 2009). In this study, the perceived age rating had a Cronbach’s alpha of α = .97, representing excellent interrater reliability.…”
Section: Methodsmentioning
confidence: 99%
“…The co-twin study also showed that 40% of the variation in perceived age is due to nongenetic factors (Christensen et al, 2009). Therefore, it is assumed that lifestyle factors can have significant long-term effects on perceived age (Gunn et al, 2015). In particular, a high social status, being married, nonsmoking, and describing no depressive mood are significantly associated with a younger appearance in comparison with chronological age from a facial photograph (Rexbye et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Aging is a fundamental process of life in which there is a time‐dependent decline of physiological integrity and cellular function affecting all tissues (Gunn et al, ; López‐Otín, Blasco, Partridge, Serrano, & Kroemer, ; Makrantonaki et al, ). In skin, these changes can occur due to the passage of time (intrinsic aging) and may be accelerated by environmental factors, the principal one being exposure to ultraviolet radiation (extrinsic aging) (Jenkins, ; Pillai, Oresajo, & Hayward, ; Tsoureli‐Nikita, Watson, & Griffiths, ).…”
Section: Introductionmentioning
confidence: 99%
“…Repeated facial expressions produce hyperfunctional facial rhytids, which progress with age, especially when associated with sun exposure, and in individuals who are heavy smokers or have poor diets (3)(4)(5)(6)(7). For some individuals, these lines are observed only with muscle contraction (dynamic rhytids), while for others, the lines are fully visible at rest (static rhytids).…”
Section: Introductionmentioning
confidence: 99%